Pola Asuh Orang Tua dalam Perkembangan Sosial Remaja di Organisasi Ikatan Pelajar Muhammadiyah Desa Kedung Banteng Tanggulangin Sidoarjo - Bahirah Naflah Rafilah; Sjafiatul Mardliyah (J+PLUS UNESA, 2026)
Parenting styles have a significant influence on shaping the social development of adolescents, especially those involved in social organizations. The purpose of this study was to describe the types of parenting styles implemented by parents and examine their impact on the social development of adolescents who are members of the Muhammadiyah Student Association (IPM) in Kedung Banteng Village, Tanggulangin, Sidoarjo. The method used in this study was a qualitative approach with a descriptive type. The subjects of the study consisted of parents and adolescents who were active members of the IPM organization in Kedung Banteng Village. Data collection was conducted through in-depth interviews, participant observation, and documentation studies. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data display, and drawing conclusions. The results of this study indicate that the dominant parenting style used by the informants' parents is democratic, although in some specific circumstances, authoritarian and permissive parenting styles are still present. Democratic parenting is characterized by open two-way interactive communication, granting freedom to choose activities accompanied by attention/supervision, and involving children in the decision-making process. The implementation of this democratic parenting style has a significant positive impact on the social development of IPM adolescents. The success of this social development is demonstrated through five main indicators: the ability to interact politely with the environment, skills in building healthy and trust-based interpersonal relationships, the ability to manage conflict wisely, independence in action, and a smooth process of searching for a positive identity through organizational activities.